2015
DOI: 10.1007/s11814-014-0315-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of tetragonal-metal-organic framework-5 loadings with extra ZnO molecule on the gas separation performance of mixed matrix membrane

Abstract: The effect of more ZnO molecule in tetragonal structure of MOF-5 than cubic structure on the gas permeation properties of T-MOF-5/polyetherimide mixed matrix membranes was investigated. T-MOF-5 was first successfully synthesized and carefully characterized by XRD, FTIR, SEM and N 2 adsorption technique at 77 K. Novel T-MOF-5/PEI MMMs were prepared using solution casting method and characterized by FTIR and SEM. The SEM pictures of the MMMs showed that T-MOF-5 nanocrystals changed the morphology of PEI and exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…MOFs are consisting of coordinated clusters with organic ligands to form a porous network. These materials have high potential for various applications such as separation and catalytic reactions . But, due to the destruction of many MOFs in the humid environment, the applications of MOF‐based mixed matrix membranes (MMMs) were severely limited in aqueous phase separations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOFs are consisting of coordinated clusters with organic ligands to form a porous network. These materials have high potential for various applications such as separation and catalytic reactions . But, due to the destruction of many MOFs in the humid environment, the applications of MOF‐based mixed matrix membranes (MMMs) were severely limited in aqueous phase separations.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, they explained the concept of unique membranes, named porous matrix membranes (PMMs) based on water‐unstable MOF crystals as a green template. The fabrication process of PMMs is similar to the conventional MMMs fabrication procedure, with a difference that after the casting of the membrane, the polymer film was then placed into the water bath followed by soaking in continuous flow water to remove MOF particles from the membrane matrix. Compared to common MMMs, the PMMs can significantly enhance the pure water permeability and this might be attributed to the changes in the physical structure of the membrane, as shown in Figure S1 .…”
Section: Introductionmentioning
confidence: 99%
“…31,32 The production of these composite materials contributes to achieving a better membrane with more acceptable specifications and transport properties than both types of polymeric and inorganic membranes, such as permeability and selectivity and suitable mechanical and thermal resistance. 32,33 Within the last decade, polymeric membranes with good chemical and thermal stability and high selectivity and gas flux, along with inorganic particles (e.g., zeolite, 34 carbon molecular sieves [35][36][37][38] , inorganic oxides, 39 and organic fillers 40 (e.g., fullerenes and carbon nanotubes (CNT) [41][42][43][44][45][46][47][48][49] , have been applied in the preparation of composite membranes. Various combinations of fillers and polymers result in diverse interface morphologies, which lead to special influences on gas-separation performance.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the ZnO cluster was primarily responsible for H 2 adsorption while the organic ligand (BDC) played only a secondary role. Arjmandi and Pakizeh (2014) synthesized and characterized (by XRD, FTIR, N 2 adsorption technique at 77 K and particle size analysis) C-MOF-5 and incorporated it in polyetherimide (PEI) as filler to make C-MOF-5/PEI MMMs and study the effect of C-MOF-5 on CH 4 , CO 2 , N 2 , and H 2 gas permeation through the MMMs. The results showed that C-MOF-5 nanocrystals have the potential (as filler in C-MOF-5/PEI MMMs) to enhance CO 2 separation from H 2 , CH 4 and N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that C-MOF-5 nanocrystals have the potential (as filler in C-MOF-5/PEI MMMs) to enhance CO 2 separation from H 2 , CH 4 and N 2 . Arjmandi et al (2014) investigated the effect of more ZnO units in T-MOF-5 than in the C-MOF-5 structure on the gas permeation properties of T-MOF-5/PEI MMMs. For this purpose, T-MOF-5 was successfully synthesized and carefully characterized by XRD, FTIR, SEM and the N 2 adsorption technique at 77 K. The results showed that T-MOF-5 nanocrystals have the potential (as filler in MMMs) to enhance H 2 separation from CO 2 , CH 4 and N 2 .…”
Section: Introductionmentioning
confidence: 99%